Performing a bone gammagraphy - Marta Corbacho Martín; Roberto Bermejo Jiménez (Fundación para el Desarrollo de la Enfermería, 2010)
In the Nuclear Medicine service multitude of diagnostic tests are performed, being one of them the bone gammagraphy that acquires a very important role both by the high demand for this test, because of its simplicity and in the realization by its high sensitivity.The bone gammagraphy as opposed to conventional radiological techniques not only provides an anatomical view, but also adds a functional imaging that provides information on bone metabolism. Addition is not restricted to malignant bone disease (primary or metastatic tumors), but it is very useful for most benign osteoarticular processes. It would be interesting to bring to the nursing knowledge of this test for a proper implementation of it, because it is a very defendant but unknown to many nurses, thus going to unify the standards of performance. The need for nursing professionals during the performance of this technique because the patient remains in these units for quite some time, being responsible for the care while they remain in the unit, taking their physical, psychological and social. We also have a key role in providing information and reassurance when the patient arrives at the unit and it is therefore necessary to have information and training necessary to answer these key questions.